2001
DOI: 10.1136/jnnp.70.3.350
|View full text |Cite
|
Sign up to set email alerts
|

Depth of lesion model in children and adolescents with moderate to severe traumatic brain injury: use of SPGR MRI to predict severity and outcome

Abstract: Objectives-The utility of a depth of lesion classification using an SPGR MRI sequence in children with moderate to severe traumatic brain injury (TBI) was examined. Clinical and depth of lesion classification measures of TBI severity were used to predict neurological and functional outcome after TBI. Methods-One hundred and six children, aged 4 to 19, with moderate to severe TBI admitted to a rehabilitation unit had an SPGR MRI sequence obtained 3 months afterTBI. Acquired images were analyzed for location, nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
43
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(49 citation statements)
references
References 36 publications
(33 reference statements)
6
43
0
Order By: Relevance
“…Patients SWI (+) group showed poor GCS and GOS comparing to that of SWI (-) group. Our data support prior studies reporting positive relationship between increasing number of hemorrhagic lesions and poor prognosis and between MBLs and neuropsychiatric deficit 3,5,8,9,12,18) . Patients with confusion and irritability (patient #6, #11, #14 and #16) mostly improved after a month, but complained intermittent headache and decrease in concentration.…”
Section: Discussionsupporting
confidence: 92%
“…Patients SWI (+) group showed poor GCS and GOS comparing to that of SWI (-) group. Our data support prior studies reporting positive relationship between increasing number of hemorrhagic lesions and poor prognosis and between MBLs and neuropsychiatric deficit 3,5,8,9,12,18) . Patients with confusion and irritability (patient #6, #11, #14 and #16) mostly improved after a month, but complained intermittent headache and decrease in concentration.…”
Section: Discussionsupporting
confidence: 92%
“…35 Examining this model relative to outcome prediction revealed that children with subcortical or brainstem lesions, present greater than 3 months postinjury on MRI, sustained significantly worse impairment as measured by disability rating scales, global outcome scores, and tests of psychosocial and cognitive function than those with cortical lesions alone. [36][37][38] These findings endorsed the concept that the lesion location and, notably, increasing depth of lesion can influence longterm outcome. Data on lesions detected early postinjury by MRI is less substantiated given that by 3 months up to 45% of patients will have lesions disappear that were present on the initial MRI.…”
supporting
confidence: 54%
“…Although there was a correlation between the total amount of microhemorrhages and the Glasgow Coma Scale (GCS) score, they found no correlation with patient outcomes measured by the Glasgow Outcome Scale (GOS). Grados et al 17 used a spoiled gradient-recalled T1-weighted MR imaging sequence to show that depth and number of lesions predicted outcome in children, though correlations were stronger with discharge outcomes compared with 1-year outcomes. Levin et al 18 showed a correlation between depth of brain lesions (by using a combination of T1, T2, and GRE sequences) and outcomes measured by the GOS score as well as the Vineland Adaptive Behavior Scale-Revised.…”
Section: Detection Of Hemorrhagic Lesionsmentioning
confidence: 99%